ANALYSIS OF FACTORS INFLUENCING REGIONAL ECONOMIC GROWTH (CASE STUDY IN SOLO RAYA 2010-2018) - Faisal Yoga Utama; Dewi Ismoyowati (MESP–FEB UNS, 2023)
This study aims to determine the effect of the degree of fiscal decentralization, capital expenditure, and human development index on regional economic growth. This research was conducted on all regencies/municipalities within the scope of the Ex-Karesidenan Surakarta in 2010-2017. The data source used in this research is secondary data taken from the Directorate General of Fiscal Balance website and the Central Bureau of Statistics which is then subjected to further data processing. The data analysis method used is multiple linear regression test using panel data. The results showed that the degree of fiscal decentralization, capital expenditure, and human development index each had a positive and significant effect on regional economic growth. In addition, the degree of fiscal decentralization, capital expenditure, and human development index simultaneously or together have a significant effect on regional economic growth.